2020
DOI: 10.18203/2349-3933.ijam20200669
|View full text |Cite
|
Sign up to set email alerts
|

A cross sectional study on stress among doctors, working in college of medicine and Sagore Dutta Hospital, Kamarhati, India

Abstract: Background: The word “stress” was defined by different scholars. The word was first defined by Hans Selye in 1936 as “a nonspecific response of the body to any demand of change”. The modern medical workplace is a complex environment, and doctors respond differently to it, some finding it stimulating and exciting, whereas others become stressed and burned. The medical workplace also provides an environment where new skills are continually being learned, both as a result of medical knowledge evolving and because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…However, in other similar studies conducted in India, maximum participants were males and age group of 25-35 years was the most common age category. [11][12][13] In our study, stress levels were assessed using PSS-10 scale and mean stress scores were found 18.40 ± 5.4. Majority (79.8%) of the participants were having moderate stress levels.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…However, in other similar studies conducted in India, maximum participants were males and age group of 25-35 years was the most common age category. [11][12][13] In our study, stress levels were assessed using PSS-10 scale and mean stress scores were found 18.40 ± 5.4. Majority (79.8%) of the participants were having moderate stress levels.…”
Section: Discussionmentioning
confidence: 74%
“…[15] In similar study conducted by Chatterjee in 2020, clinical interns showed maximum levels of the stress with mean scores of 20.4 ± 5.2 followed by house residents (17.5 ± 5.1). [13] This showed that beginning of the career induces more stress to the health-care providers. Similar findings were seen in the studies conducted by Sahasrabuddhe et al [1] and Lorga et al [16] In other study, main stress factors were mentioned as heavy work load with long duty hours (48.3%), poor accommodation and food (32%), low stipend (41%), and lack of social and family life (22.8%).…”
Section: Discussionmentioning
confidence: 99%
“…The word 'stress' was first coined by Seyle in 1936 to define a non-specific body response to any need for change (3). Stress is a harmful response both physical or emotional, occurring due to an imbalance between job requirements and the employee's capabilities, resources or needs (8).…”
Section: Discussionmentioning
confidence: 99%
“…Hans Selye coined the term "stress" in 1936, defining it as "the body's non-specific reaction to any demand for change". 1 The feeling of stress occurs when people do not have the resources to meet the demands placed on them.…”
Section: Introductionmentioning
confidence: 99%